2005
DOI: 10.1063/1.1869549
|View full text |Cite
|
Sign up to set email alerts
|

Electron field emission from GaN nanorod films grown on Si substrates with native silicon oxides

Abstract: GaN nanorod films have been grown on Si(001) substrates with native silicon oxides by radio-frequency plasma-enhanced molecular beam epitaxy. GaN nanorod films are made up of single-crystalline nanorods with a so-called (0001) fiber-like texture. Each nanorod is elongated along c axis in perpendicular to the substrate surface and has no preferential axis in film plane. Excellent electron field emission characteristics were observed for the fabricated GaN nanorod films with a field emission threshold as low as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
47
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…For the synthesis of GaN based nanostructures several techniques have been used, for example, metal-organic chemical vapor deposition [8], laser ablation [9], molecular beam epitaxy [10], the solgel method [11], template-induced growth [12], sublimation method [13], halide vapor phase epitaxy (HVPE) [14] and conversion of amorphous gallium oxide nanotubes [15]. Among the various kinds of fabrication methods, HVPE is an attractive technique since it has the advantages of high growth rate and relatively low cost.…”
Section: Introductionmentioning
confidence: 99%
“…For the synthesis of GaN based nanostructures several techniques have been used, for example, metal-organic chemical vapor deposition [8], laser ablation [9], molecular beam epitaxy [10], the solgel method [11], template-induced growth [12], sublimation method [13], halide vapor phase epitaxy (HVPE) [14] and conversion of amorphous gallium oxide nanotubes [15]. Among the various kinds of fabrication methods, HVPE is an attractive technique since it has the advantages of high growth rate and relatively low cost.…”
Section: Introductionmentioning
confidence: 99%
“…2 in Ref. [3]). Such interface roughness is thought to influence the growth direction of the nanorods.…”
mentioning
confidence: 91%
“…We have recently grown highly crystalline hexagonal GaN nanorods on Si(100) substrates with native silicon oxides by radio frequency (RF) plasma-assisted molecular beam epitaxy (MBE). We have reported that the one-dimensionality and highly c-axis orientation of hexagonal GaN nanorods, as well as their strong chemical and mechanical stability and low electron affinity of 2.7-3.2 eV, result in excellent field emission characteristics [3,4]. It has also been reported that during MBE growth, sharp-pointed structures are formed on the top of GaN nanorods, and that each nanorod is single crystallite with low defect density [3,5].…”
mentioning
confidence: 96%
“…Recently, we have grown highly c-oriented hexagonal GaN nanorods on Si(001) substrates with native silicon oxides (SiO 2 ) by RF-plasma-assisted MBE (RF-MBE) under nitrogen-rich conditions [6]. GaN nanorods show excellent photoluminescence due to their dislocation-free nature.…”
mentioning
confidence: 99%